176k views
4 votes
12(x-2)+3x=1/2(x+6) +2

User Ppetrid
by
5.3k points

2 Answers

4 votes

Answer:

X = 2

Explanation:

Let's solve your equation step-by-step.

12(x−2)+3x=1/2(x+6)+2

Step 1: Simplify both sides of the equation.

12(x−2)+3x=1/2(x+6)+2

(12)(x)+(12)(−2)+3x=(1/2)(x)+(1/2)(6)+2(Distribute)

12x+−24+3x=1/2x+3+2

15x+−24=1/2x+5

15x−24=1/2x+5

Step 2: Subtract 1/2x from both sides.

15x−24−1/2x=1/2x+5−1/2x


(29)/(2)x−24=5

Step 3: Add 24 to both sides.


(29)/(2)x−24+24=5+24


(29)/(2)x = 29

Step 4: Multiply both sides by 2/29.

(
(29)/(2))*(
(29)/(2)x)=(
(29)/(2))*(29)

x = 2

User Dasilvj
by
5.4k points
5 votes

Answer: I think your answer is 2 ( please let me know if this is wrong ) !

Explanation:

User Shoham Yetzhak
by
4.9k points